Study on the Growth Performance of Bamboo Species Melocanna baccifera and Dendrocalamus longispathus along with Crop (Glycine max) in Degraded Jhum Land of Mizoram - Jha, L. K.; , Lalnuntluanga; Marak, Ch. (Indian Forester, 2004)
No abstract